Sidewall rubber composition containing modified lignin and mixing method thereof
Through citric acid graft-modified lignin and wet flocculation and mixing technology, the problem of poor lignin dispersion in rubber is solved, and the rubber performance is improved and the production process is environmentally friendly and efficient.
Patent Information
- Application Number
- CN202510133303.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-06
AI Technical Summary
The prior art is difficult to achieve nano-scale dispersion of lignin in rubber, resulting in limited improvement in performance in rubber, and traditional dry mixing has problems such as dust pollution, high energy consumption, and high heat generation.
The lignin is grafted and modified by citric acid to enhance its hydrophilicity. The wet kneading method is used and flocculation technology is combined to improve the dispersion of lignin in rubber.
It realizes efficient dispersion of lignin in rubber, reduces the rolling resistance of the rubber composition, enhances the rubber network strength, improves tensile performance, and avoids the pollution and high energy consumption problems of traditional dry mixing.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tire rubber manufacturing, in particular to a sidewall rubber composition containing modified lignin and a mixing method thereof. Background Art
[0002] Due to the non-renewable nature of fossil fuel resources and the environmental pollution and greenhouse gas emissions caused by their use, countries around the world are seeking new energy sources as a way out for sustainable development. Therefore, biomass energy, as a renewable energy source with a wide range of sources, and the development and utilization of biomass-based materials have also received widespread attention.
[0003] Lignin is one of the main components of higher plants. Using lignin as a filler to fill rubber can not only strengthen rubber, replace carbon black, and get rid of dependence on petroleum, but also reduce production costs. At the same time, it can give rubber excellent flame retardancy, UV resistance, and antioxidant properties, making the application and research and development of lignin in rubber very cutting-edge. However, due to the complexity and heterogeneity of the chemical and physical structures of lignin, it is difficult to truly form a nano-scale dispersion in the rubber matrix to achieve performance similar to that of carbon black-reinforced rubber, and sometimes even deteriorate the performance of the material. Therefore, there is still a very long way to go before lignin can completely replace carbon black and be used in most rubbers, especially general non-polar rubbers. In view of this, how to make lignin into a filler with the same reinforcing properties as traditional fillers and apply it to rubber will be a very promising direction.
[0004] The Chinese invention patent (publication number: CN117757159A, publication date: 2024-03-26) discloses a tire rubber composition, which is prepared by mixing the following raw materials by weight based on 100 parts by weight of raw rubber: 100 parts of raw rubber, 45-80 parts of reinforcing filler; and an appropriate amount of activator, antioxidant and vulcanizer; the raw rubber includes 5-15 parts of trans-isoprene rubber, and the reinforcing filler includes 5-20 parts of lignin-modified white carbon black, and the lignin-modified white carbon black is prepared by reacting the following raw materials based on 100 parts by weight of white carbon black: 100 parts of white carbon black, 10-60 parts of acetylated lignin. The composition solves the problem of increased heat generation after adding trans-isoprene rubber by modifying white carbon black with acetylated lignin. The prepared mining tire has good tear resistance, puncture resistance, cutting resistance, and chipping resistance, while reducing the heat generation of the rubber compound.
[0005] A Chinese invention patent (publication number: CN112831059B, publication date: 2021-11-26) discloses a modified lignin, a preparation method thereof, and an application in a rubber composite material. Lignin is reacted with an alkynyl compound in an organic solvent to obtain a reaction solution containing modified lignin. The present invention has the following advantages: (1) The alkynylating agent contains an acyl chloride functional group in its structure, which is easy to undergo esterification reaction with the alcohol hydroxyl group and phenolic hydroxyl group in the lignin molecule to generate modified lignin grafted with unsaturated alkynyl functional groups. (2) Alkynylation modification reduces the hydroxyl content in the lignin molecule and reduces the molecular polarity, which helps to inhibit the self-aggregation tendency of lignin caused by hydrogen bonds, is conducive to grinding to obtain lignin powder with a smaller particle size, improves the compatibility and affinity of lignin with non-polar natural rubber, and promotes the dispersion of lignin in the natural rubber matrix.
[0006] In addition, in traditional dry mixing, the shearing and crushing effect of open mills and internal mixers is used to mix the compounding agent and the rubber material. This mixing method not only has problems such as dust pollution, high energy consumption, and high heat generation, but also has poor dispersibility for fillers that are easy to self-aggregate and difficult to disperse, such as lignin and white carbon black. The advantages of wet mixing are more significant. Summary of the invention
[0007] The present invention aims at the deficiencies of the prior art and provides a sidewall rubber composition containing modified lignin and a mixing method thereof. The modified lignin used in the sidewall can effectively replace carbon black to prepare the sidewall rubber composition and improve the dispersibility of lignin in rubber.
[0008] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions: A sidewall rubber composition containing modified lignin, wherein the rubber composition is prepared by wet mixing by mixing raw materials including the following components per 100 parts by weight of raw rubber: Natural rubber 25.0-55.0 parts, Butadiene rubber 45.0-75.0 parts, Carbon black 25.0-55.0 parts, 5.0-15.0 parts of modified lignin, Rubber operating oil 1.0-10.0 parts, 1.0-4.0 parts of tackifying resin, Paraffin 1.0-4.0 parts; The modified lignin is water-soluble lignin obtained by modifying lignin by grafting citric acid groups.
[0009] Preferably, the rubber composition is prepared by mixing the following raw materials based on 100 parts by weight of raw rubber: Natural rubber 35.0-45.0 parts, Butadiene rubber 55.0-65.0 parts, Carbon black 35.0-45.0 parts, Modified lignin 8.0-12.0 parts, Rubber operating oil 1.0-3.0 parts, Anti-aging agent 1.0-6.0 parts, 2.5-3.5 parts of tackifying resin, 1.5-2.5 parts of paraffin wax, Active agent 1.0-5.0 parts, Accelerator 0.5-3.0 parts, Vulcanizing agent 1.0-4.0 parts.
[0010] Preferably, the modified lignin is lignin in which citric acid groups are grafted onto the lignin groups under the catalytic action of sodium hypophosphite to enhance its hydrophilicity.
[0011] Preferably, the preparation method of modified lignin comprises the following steps: 1) At room temperature, citric acid is dissolved in water to prepare a citric acid solution, sodium hypophosphite is added, and the solution is stirred to mix evenly; the lignin nanoparticle powder obtained by freeze drying is added, and stirring is continued for 0.5-1.5 hours to allow the lignin nanoparticles to fully contact with the citric acid aqueous solution to obtain a suspension; 2) Place the suspension in a vacuum drying oven and let it stand at room temperature for 11-13 hours after evacuating the vacuum; 3) placing the suspension in an air drying oven to remove excess water and colloidal substances, and then placing the remainder at 125-135° C. for 3.5-4.5 hours, and taking out the colloidal lignin nanoparticles after the reaction is completed; 4) re-dispersing the colloidal lignin nanoparticles in water and purifying the modified lignin nanoparticles by centrifugation, dialyzing the precipitate obtained after centrifugation in deionized water, diluting the modified lignin nanoparticle suspension to less than 1%, and dispersing it evenly in water after ultrasonic treatment; 5) Freeze drying to obtain modified lignin.
[0012] Preferably, the concentration of the citric acid solution is 4-6% (w / w); And / or, the concentration of sodium hypophosphite is 1% (w / w); And / or, the vacuum degree of the vacuum drying oven is 0.5-0.7 Bar, and the suspension is placed for 1.5-2.5 hours; and / or, the air drying oven temperature is 55-65° C., and the suspension is placed for 46-50 hours; And / or, the freeze-drying temperature is -45°C to -55°C, and the vacuum degree is 0.11-0.13 mBar.
[0013] Preferably, the wet mixing comprises the following steps: mixing carbon black, modified lignin and water to obtain dispersion A, mixing rubber and deionized water to obtain dispersion B, mixing dispersion A and dispersion B, then adding CaCl2 aqueous solution to flocculate them to obtain flocculent gel, washing and drying the flocculent gel to obtain a masterbatch, and placing the masterbatch and compounding agents in an open mill to mix and obtain a wet mixed rubber.
[0014] Preferably, the carbon black particle size is 30-70 nm.
[0015] Preferably, the active agent is zinc oxide and stearic acid, with zinc oxide accounting for 1.0-4.0 parts and stearic acid accounting for 1.0-3.0 parts.
[0016] Preferably, the accelerator is accelerator CZ and / or accelerator NS, the accelerator CZ is 0.1-2.0 parts, and the accelerator NS is 0.1-0.65 parts.
[0017] Furthermore, the present invention also discloses a mixing method for the sidewall rubber composition containing modified lignin, which adopts a wet mixing method and comprises the following steps: 1) Preparation of masterbatch a. Put carbon black, modified lignin and water into a colloid mill and grind them to obtain a carbon black aqueous dispersion; b. Add deionized water to the rubber to adjust the solid content to 10%, then transfer to a beaker and stir evenly with an electric stirrer at a speed of 450-550 rpm and a stirring time of 8-12 minutes; c. Add the carbon black aqueous dispersion to the uniformly mixed rubber, continue stirring for 25-35 minutes, and drop 5% by mass fraction of CaCl2 aqueous solution into the mixed solution to make it flocculate; d. Wash the flocculent gel in deionized water for 4-6 times, and then dry it in a vacuum oven at 55-65°C for 22-26 hours to obtain a masterbatch; 2) Mixing a. Heat the hot roll mill to 75-90℃, add the masterbatch into the mill and plasticize for 0.5-1.5min until it wraps around the roll; b. Add rubber operating oil, tackifying resin, paraffin, zinc oxide, stearic acid, antioxidant, accelerator and vulcanizer in sequence, tap the rubber continuously to make the compounding agents evenly dispersed in the rubber, then adjust the roller distance to 0.15-0.25mm, make triangle packages and roll them in sequence, repeat three times, then adjust the roller distance to 1.5-2.0mm, produce sheets, and obtain wet mixed rubber.
[0018] The beneficial effects of the present invention are as follows: the present invention uses citric acid to modify lignin, grafts citric acid groups on lignin groups to enhance their hydrophilicity, and combines with wet mixing to effectively improve the dispersibility of lignin in rubber and reduce the rolling resistance of the rubber composition. At the same time, the addition of lignin can enhance the strength of the rubber network and improve the tensile properties of the rubber.
[0019] In the rubber composition of the present invention, in addition to the above-mentioned components, different additives can be mixed, such as other fillers commonly used in tires and other rubber compositions, vulcanizing agents, vulcanization accelerators, different types of oils, antioxidants, plasticizers, etc. These additives are mixed in a common way to obtain a rubber composition that can be used for vulcanization. The amount of these additives can also be a conventional, usually mixed amount, provided that the purpose of the present invention is not adversely affected. DETAILED DESCRIPTION
[0020] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] The formulations of the embodiments and comparative examples are shown in Table 1 (parts by weight).
[0022] Table 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Example 1 Example 2 Example 3 Natural rubber*1 40 40 40 40 40 40 40 40 Butadiene rubber*2 30 30 30 30 30 30 30 Butadiene rubber*3 60 30 30 30 30 30 30 30 Carbon black*4 5 Carbon black*5 35 35 48 35 35 35 35 35 Carbon black*6 5 5 5 5 5 5 5 Modified lignin 20 5 10 15 Lignin*7 10 Rubber operating oil*8 2 2 2 2 2 2 2 2 Stearic acid*9 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 Anti-aging agent*10 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 Antiaging agent*11 2.5 2.5 2.5 2.5 2.5 2.5 2.5 2.5 Zinc oxide*12 3 3 3 3 3 3 3 3 Paraffin*13 2 2 2 2 2 2 2 2 Tackifying resin*14 3 3 3 3 3 3 3 3 Accelerator*15 0.25 0.25 0.25 0.25 0.25 0.25 0.25 0.25 Accelerator*16 0.65 0.65 0.65 0.65 0.65 0.65 0.65 0.65 Oil-filled sulfur*17 2 2 2 2 2 2 2 2 Table 1 Footnotes *1: Natural rubber (solid content 60%), a product of China National Rubber Group; *2: BR1250H, a product of ZEON, Japan; *3: BR9000, a product of Zhejiang Chuanhua Company; *4: N330, product of Cabot Chemical Company; *5: N550, product of Cabot Chemical Company; *6: N660, product of Cabot Chemical Company; *7: Lignin HS-L101, product of Hangshi Technology Development Co., Ltd.; *8: V500, product of Ningbo Hansheng Co., Ltd. *9: Stearic acid SA1801, a product of Yihai Kerry; *10: Antioxidant RD, a product of Sinopec Nanjing Chemical Industry Co., Ltd.; *11: Antioxidant 4020, a product of Sinopec Nanjing Chemical Industry Co., Ltd.; *12: Zinc oxide, product of Qingdao Haiyan Chemical Co., Ltd.; *13: Microcrystalline wax H3236, a product of Yanggu Huatai; *14: Tackifying resin SL-1801, Huaqi Chemical Products; *15: Accelerator CZ, a product of Shandong Shangshun Chemical Co., Ltd.; *16: Accelerator NS, a product of Shandong Shangshun Chemical Co., Ltd.; *17: Oil-filled sulfur powder, a product of Wuxi Huasheng Rubber New Material Technology Co., Ltd.
[0023] Comparative Example 1 adopts dry mixing, and the other comparative examples and embodiments adopt wet mixing.
[0024] The specific steps of dry mixing are as follows: 1) One-stage mixing: Use internal mixer for mixing; add rubber, press down the mass and keep it for 60 seconds; lift the mass, add carbon black, activator and antioxidant, press down the mass and keep it for 60 seconds; lift the mass and add rubber operating oil, tackifying resin and paraffin, press down the mass and keep it for 90 seconds; lift the mass and clean it; 2) Second stage mixing: Use open mill for mixing; discharge rubber to open mill, adjust the roller distance of double-roll open mill to 1.0mm, so that the rubber compound after mixing is wrapped around the roller; add accelerator and vulcanizer in sequence, cut the left and right knives three times each; make triangle wrapping passes five times when the roller is 0.20mm; adjust the roller distance to 2.0mm, remove the sheet and park.
[0025] The specific steps of wet mixing are as follows: 1) Preparation of masterbatch a. Put carbon black, modified lignin and 500 mL of water into a colloid mill and grind them to obtain a carbon black aqueous dispersion; b. Add deionized water to the rubber to adjust the solid content to 10%, then transfer to a beaker and stir evenly with an electric stirrer at a stirring speed of 500 rpm for 10 minutes; c. Add the carbon black aqueous dispersion to the uniformly mixed rubber, continue stirring for 30 minutes, and drop 650 mL of 5.0% CaCl2 aqueous solution into the mixture to make it flocculate; d. The flocculent gel was washed in deionized water for 5 times, and then dried in a vacuum oven at 60° C. for 24 h to obtain a masterbatch; 2) Mixing a. Heat the hot roll mill to 80℃, add the masterbatch into the mill and plasticize for 1.0min until it wraps around the roll; b. Add rubber operating oil, tackifying resin, paraffin, zinc oxide, stearic acid, antioxidant, accelerator and vulcanizer in sequence, tapping the rubber continuously to make the compounding agents evenly dispersed in the rubber, then reduce the roller distance to 0.20mm, make triangle packages and roll them in sequence, repeat three times, then adjust the roller distance to 2.0mm, produce sheets, and obtain wet mixed rubber.
[0026] The rubber compositions obtained in the examples and comparative examples were tested.
[0027] Vulcanization characteristics: According to GB / T 9869-1997 standard, the UR-2030 rotorless vulcanizer of UCONN was used to measure the vulcanization curve and vulcanization characteristic parameters at 143°C and a swing angle of 1°.
[0028] Filler dispersion: The blended rubber was tested using the RPA2000 rubber processing analyzer from Alpha Corporation in the United States. 5-6 g of the mixed rubber was placed in the mold cavity and tested at 60°C to analyze and study the effects of different mixing methods and different blending ratios on the filler network of the blended rubber.
[0029] Tensile properties: The tensile strength and tear strength of the composite materials are in accordance with GB / T 528-2009 and GB / T 529-2008 standards. The tensile specimen is dumbbell-shaped and the tearing specimen is right-angled. The test is carried out using a U-CAN UT-2060 electronic tensile testing machine at a rate of 500 mm / min.
[0030] Dynamic mechanical analysis (DMA) was performed in tensile mode on a DMA 242D dynamic mechanical analyzer produced by NETZSCH, Germany. The test conditions were: 12 Hz, 0.5% strain, temperature range: -100-100℃, heating rate 3℃ / min.
[0031] The test data is shown in Table 2.
[0032] Table 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Example 1 Example 2 Example 3 T90(min) 100 95 93 92 90 93 91 90 Payne effect (%) 100 32 95 90 32 30 26 31 TB(MPa) 100 109 121 111 93 123 128 116 EB(%) 100 109 86 106 112 116 128 111 Tan delta 60℃ 100 83 96 86 78 72 73 76 Analyzing Table 2, Example 2 is the best example with the best comprehensive performance. It can be seen from Comparative Examples 1 and 2 that the filler dispersibility of wet mixing is significantly higher, the tensile properties of the rubber composition are better, and the rolling resistance is relatively low. Comparative Example 2 and Example 2 add an equal amount of carbon black, and Comparative Example 3 adds a sufficient amount of carbon black. It can be seen that the filler dispersibility of Example 2 is significantly improved, the network strength of the rubber is also significantly improved, the tensile properties are significantly enhanced, and the rolling resistance is relatively low. Lignin can effectively replace part of the carbon black. It can be seen from Comparative Example 4 and Example 2 that lignin modification can effectively improve hydrophilicity so as to better adapt to wet mixing and effectively improve the dispersibility of lignin in rubber. It can be seen from Comparative Example 5 and the examples that the amount of modified lignin added should not be too much.
[0033] The above is a description of the embodiments of the present invention. Through the above description of the disclosed embodiments, professionals and technicians in the field can implement or use the present invention. Various modifications to these embodiments will be apparent to professionals and technicians in the field. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown in this article, but will conform to the widest range consistent with the principles and novelties disclosed herein.
Claims
1. A sidewall rubber composition containing modified lignin, characterized in that: The rubber composition is prepared by wet mixing, and the raw materials including the following components are mixed based on 100 parts by weight of raw rubber: Natural rubber 25.0-55.0 parts, Butadiene rubber 45.0-75.0 parts, Carbon black 25.0-55.0 parts, 5.0-15.0 parts of modified lignin, Rubber operating oil 1.0-10.0 parts, 1.0-4.0 parts of tackifying resin, Paraffin 1.0-4.0 parts; The modified lignin is water-soluble lignin obtained by modifying lignin by grafting citric acid groups.
2. A sidewall rubber composition containing modified lignin according to claim 1, characterized in that: The rubber composition is prepared by mixing the following raw materials based on 100 parts by weight of raw rubber: Natural rubber 35.0-45.0 parts, Butadiene rubber 55.0-65.0 parts, Carbon black 35.0-45.0 parts, Modified lignin 8.0-12.0 parts, Rubber operating oil 1.0-3.0 parts, Anti-aging agent 1.0-6.0 parts, 2.5-3.5 parts of tackifying resin, 1.5-2.5 parts of paraffin wax, Active agent 1.0-5.0 parts, Accelerator 0.5-3.0 parts, Vulcanizing agent 1.0-4.0 parts.
3. A sidewall rubber composition containing modified lignin according to claim 1 or 2, characterized in that: The modified lignin is prepared by grafting citric acid groups onto the lignin groups under the catalytic action of sodium hypophosphite to enhance the hydrophilicity of the lignin.
4. A sidewall rubber composition containing modified lignin according to claim 1 or 2, characterized in that: The preparation method of modified lignin comprises the following steps: 1) At room temperature, citric acid is dissolved in water to prepare a citric acid solution, sodium hypophosphite is added, and the solution is stirred to mix evenly; the lignin nanoparticle powder obtained by freeze drying is added, and stirring is continued for 0.5-1.5 hours to allow the lignin nanoparticles to fully contact with the citric acid aqueous solution to obtain a suspension; 2) Place the suspension in a vacuum drying oven and let it stand at room temperature for 11-13 hours after evacuating the vacuum; 3) placing the suspension in an air drying oven to remove excess water and colloidal substances, and then placing the remainder at 125-135° C. for 3.5-4.5 hours, and taking out the colloidal lignin nanoparticles after the reaction is completed; 4) re-dispersing the colloidal lignin nanoparticles in water and purifying the modified lignin nanoparticles by centrifugation, dialyzing the precipitate obtained after centrifugation in deionized water, diluting the modified lignin nanoparticle suspension to less than 1%, and dispersing it evenly in water after ultrasonic treatment; 5) Freeze drying to obtain modified lignin.
5. A sidewall rubber composition containing modified lignin according to claim 4, characterized in that: The concentration of the citric acid solution is 4-6% (w / w); And / or, the sodium hypophosphite concentration is 0.8-2.0% (w / w); And / or, the vacuum degree of the vacuum drying oven is 0.5-0.7 Bar, and the suspension is placed for 1.5-2.5 hours; and / or, the air drying oven temperature is 55-65° C., and the suspension is placed for 46-50 hours; And / or, the freeze-drying temperature is -45°C to -55°C, and the vacuum degree is 0.11-0.13 mBar.
6. A sidewall rubber composition containing modified lignin according to claim 1 or 2, characterized in that: The wet mixing comprises the following steps: mixing carbon black, modified lignin and water to obtain dispersion A, mixing rubber and deionized water to obtain dispersion B, mixing dispersion A and dispersion B evenly, then adding CaCl2 aqueous solution to flocculate them to obtain flocculent gel, washing and drying the flocculent gel to obtain a masterbatch, and placing the masterbatch and compounding agents in an open mill for mixing to obtain a wet mixed rubber.
7. A sidewall rubber composition containing modified lignin according to claim 1 or 2, characterized in that: The carbon black particle size is 30-70nm.
8. The sidewall rubber composition containing modified lignin according to claim 2, characterized in that: The active agent is zinc oxide and stearic acid, with the zinc oxide accounting for 1.0-4.0 parts and the stearic acid accounting for 1.0-3.0 parts.
9. The sidewall rubber composition containing modified lignin according to claim 2, characterized in that: The accelerator is accelerator CZ and / or accelerator NS, the accelerator CZ is 0.1-2.0 parts, and the accelerator NS is 0.1-0.65 parts.
10. A mixing method for a sidewall rubber composition containing modified lignin according to any one of claims 1 to 9, characterized in that: The wet mixing method includes the following steps: 1) Preparation of masterbatch a. Put carbon black, modified lignin and water into a colloid mill and grind them to obtain a carbon black aqueous dispersion; b. Add deionized water to the rubber to adjust the solid content to 10%, then transfer to a beaker and stir evenly with an electric stirrer at a speed of 450-550 rpm and a stirring time of 8-12 minutes; c. Add the carbon black aqueous dispersion to the uniformly mixed rubber, continue stirring for 25-35 minutes, and drop 5% by mass fraction of CaCl2 aqueous solution into the mixed solution to make it flocculate; d. Wash the flocculent gel in deionized water for 4-6 times, and then dry it in a vacuum oven at 55-65°C for 22-26 hours to obtain a masterbatch; 2) Mixing a. Heat the hot roll mill to 75-90℃, add the masterbatch into the mill and plasticize for 0.5-1.5min until it wraps around the roll; b. Add rubber operating oil, tackifying resin, paraffin, zinc oxide, stearic acid, antioxidant, accelerator and vulcanizer in sequence, tap the rubber continuously to make the compounding agents evenly dispersed in the rubber, then adjust the roller distance to 0.15-0.25mm, make triangle packages and roll them in sequence, repeat three times, then adjust the roller distance to 1.5-2.0mm, produce sheets, and obtain wet mixed rubber.
Citation Information
Patent Citations
A modified lignin, its preparation method, and its application in rubber composites.
CN112831059B
Application of lignin modified white carbon black in enhancement of trans-isoprene rubber crystal and preparation of mine tire
CN117757159A
Industrial lignin reinforcing rubber and preparation method of industrial lignin reinforcing rubber
CN102718995A
Rubber composition containing rubber modifier, vulcanized rubber, as well as preparation method and application thereof
CN111763358A
Degradable PPC composite board and preparation method thereof
CN114106537A